Sosialisasi Pemanfaatan Media Pembelajaran Intraktif Menggunakan Google Slide di SMP N 4 Mauliru - Deku, Juwita Padu; Kii, Rosalia Arinita Ina; Buana, Enjelina Rambu; Muna, Dinintia Rambu Yaku; Henjang, Airinsia Habi; Ndapa Huda, Marleni Rosalia (Universitas Negeri Gorontalo, 2025)
This community service aims to improve the ability of teachers and students to use Google Slide as an interactive learning media at SMP Negeri 4 Mauliru. This activity is motivated by the still low mastery of information technology, especially in creating digital-based learning media among teachers. Meanwhile, mastery of media such as Google Slide is essential to support teacher pedagogical competence, especially in designing, implementing, and evaluating learning that is interesting, effective, and in accordance with student characteristics. The method of implementing the activity includes preparation, implementation, and evaluation. Three teachers and 24 students attended this activity. The results of the activity showed that the use of Google Slides can increase student motivation and active participation while also helping teachers deliver material more creatively and in a structured manner. Evaluation of the activity through observation and reflection showed an increase in teachers' understanding of Google Slide features and their ability to compile digital teaching materials.